Exploration and Exploitation in Organizational Learning: A Critical Application of the 4I Model. (30th August 2018) - Nielsen, Jeppe Agger; Mathiassen, Lars; Hansen, Anne Mette
Abstract: While it is broadly agreed that managers face tensions between exploration of new possibilities and exploitation of existing certainties, there are open questions related to how they can recognize these tensions and distribute resources between the two forms of learning across time and space. The heavily cited 4I Model made significant progress towards addressing these questions, based on the idea that exploration and exploitation unfold differently across organizational levels, with exploration as feed‐forward from the individual towards the organizational level, and exploitation as feedback from the organizational towards the individual level. The authors' critical application of the model questions this idea, suggesting that exploration and exploitation unfold through similar patterns from the individual level towards the organizational level with iterative feedback loops. This repositioning of the 4I Model affords a detailed understanding of both exploration and exploitation processes as well as the temporal and spatial interactions between them. To demonstrate the utility of this theorizing and to add new insights to the process literature on organizational learning, the authors rely on a longitudinal case study of how a management team engaged in technology‐enabled strategic renewal in a Danish local government organization.